2016
DOI: 10.3390/nu8060318
|View full text |Cite
|
Sign up to set email alerts
|

Cuminaldehyde from Cinnamomum verum Induces Cell Death through Targeting Topoisomerase 1 and 2 in Human Colorectal Adenocarcinoma COLO 205 Cells

Abstract: Cinnamomum verum, also called true cinnamon tree, is employed to make the seasoning cinnamon. Furthermore, the plant has been used as a traditional Chinese herbal medication. We explored the anticancer effect of cuminaldehyde, an ingredient of the cortex of the plant, as well as the molecular biomarkers associated with carcinogenesis in human colorectal adenocarcinoma COLO 205 cells. The results show that cuminaldehyde suppressed growth and induced apoptosis, as proved by depletion of the mitochondrial membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 64 publications
1
16
0
Order By: Relevance
“…Interestingly, similarly to our synergistic data using carvacrol and farnesol, carvacrol has been reported to have synergistic interactions with fluconazole against the planktonic and biofilm forms of C. albicans [59]. Furthermore, carvacrol has been classified as GRAS (generally recognized as safe) and approved for food use [60], as has cuminaldehyde [61]. The results from this study can be employed both for the prevention of biofilm formation by single or mixed species and for their treatment.…”
Section: Discussionsupporting
confidence: 79%
“…Interestingly, similarly to our synergistic data using carvacrol and farnesol, carvacrol has been reported to have synergistic interactions with fluconazole against the planktonic and biofilm forms of C. albicans [59]. Furthermore, carvacrol has been classified as GRAS (generally recognized as safe) and approved for food use [60], as has cuminaldehyde [61]. The results from this study can be employed both for the prevention of biofilm formation by single or mixed species and for their treatment.…”
Section: Discussionsupporting
confidence: 79%
“…The highest turnover rate for Pe AAO2 was observed for cumic alcohol oxidation to the bioactive compound cuminaldehyde, a major constituent of seed oil of Cuminum cyminum plant (Lee 2005 ; Li and Jiang 2004 ). Beyond the use of C. cyminum seeds as spice in traditional cuisines, different beneficial effects have been attributed to its use, including anticancer, antidiabetic, and neuroprotective effects that have been linked to cuminaldehyde as its active ingredient (Lee 2005 ; Morshedi et al 2015 ; Patil et al 2013 ; Tsai et al 2016 ). The biocatalytic production of cuminaldehyde has not been described yet and the oxidation of cumic alcohol to cuminaldehyde using Pe AAO2 seems to be a feasible route.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, EOs and their constituents have been investigated as an alternative additive in the food industry [ 44 , 59 ] in contrast to synthetic antioxidants, such as butylated hydroxytoluene, butylated hydroxyanisole, and propyl gallate, that have exhibited undesired effects to human health [ 60 , 61 ]. Natural compounds from plant EOs which have shown biological activities with potential pharmaceutical applications include ( E )-cinnamaldehyde (antifungal activity, Figure 1 panel A) [ 62 ]; menthol and L-menthol (analgesic activity, panels B and C) [ 63 ]; cuminaldehyde (anticancer activity, panel D) [ 64 ]; eucalyptol and eugenol (anti-inflammatory activity, panels E and F) [ 65 , 66 , 67 ]; and thymol, carvacrol, and methyl chavicol (antioxidant activities, panels G, H, and I) [ 68 , 69 ]. It is important to note that some well-known compounds found in EOs have been recently described with new biological activities, e.g., monoterpenes such as thymol, carvacrol, and p -cymene have been reported to reduce lung emphysema and inflammation [ 70 ] and eugenol has shown activity against several parasites with clinical relevance [ 71 , 72 ].…”
Section: Bioactive Compounds From Eos Of Spice Plantsmentioning
confidence: 99%
“…Regarding the anticancer activity, a study demonstrated that cuminaldehyde, a component from the true cinnamon tree’s bark, has cytotoxicity against human colorectal adenocarcinoma cells (COLO 205) through targeting Topoisomerase I and II, which are relevant molecular targets for cancer therapy [ 64 ]. Unlu et al [ 88 ] demonstrated the cytotoxic activity of EOs of C. zeylanicum composed of major compounds ( E )-cinnamaldehyde (68.95%), benzaldehyde (9.94%), and ( E )-cinnamyl acetate (7.44%) against F2408 (normal rat fibroblasts) and 5RP7 (H-ras active-rat fibroblasts) cell lines.…”
Section: Bioactive Compounds From Eos Of Spice Plantsmentioning
confidence: 99%